Meningkatkan keterampilan penalaran ilmiah tentang topik ekosistem melalui laboratorium virtual gizmos - Nadiyyatul Husna; Safwatun Nida; Firda Awalia Putri (Universitas Negeri Jakarta, 2026)
Scientific reasoning skills are fundamental in biology education, yet their development remains a challenge in conventional learning. Virtual laboratories like Gizmos offer a promising alternative to address this issue. Therefore, this study aimed to analyze the effect of the Gizmos virtual laboratory on seventh-grade students' scientific reasoning skills on the ecosystem topic. This study employed a one-group pretest-posttest design, with data collected through a scientific reasoning test and a student response questionnaire. The results showed a significant improvement in students' scientific reasoning skills (p < 0.05) with a moderate N-gain score. Furthermore, students demonstrated positive responses towards the virtual laboratory, although some technical challenges were reported. These findings suggest that the Gizmos virtual laboratory is an effective tool for enhancing scientific reasoning in biology education, with teacher guidance being crucial for optimal implementation.